Violent discipline, and cognitive and socio-emotional development in the preschool infant - Pazos Polo, Daniela (2021)
The general objective of the study was to describe the relationship between the style of discipline exercised by the teacher in the 4-year-old classroom of a private educational institution in Lima, and the cognitive and socio-emotional development of the students. In this research, of a qualitative descriptive nature, a field notebook and a semi-structured interview for the teacher were used. Among the most relevant findings, it stands out that the pedagogical practices applied in the classroom mainly violate and harm the socio-emotional development of their students, which generates distraction and disinterest in class. This, in turn, could be associated with the poor academic performance of students. It was concluded that the teacher needs to apply pertinent and adequate pedagogical strategies according to the needs of the group of infants.